Tradisi Ngalak Kontrak pada Jual Beli Buah Kopi dalam Perspektif Maqashid Al-Shari’ah di Desa Karangpring, Kecamatan Sukorambi, Kebupaten Jember - Ahmad Muhyidin (IJIEF: Indonesian Journal of Islamic Economics and Finance, 2019)
This paper will discuss the Ngalak contract tradition among the coffee fruit farmer in the maqashid al-sharia perspective. This paper aims to analyze how the Ngalak contract tradition in complying with maqashid al-sharia. By using a qualitative approach, this paper will explain the social phenomena about the local wisdom in Karangpring Village, Sukorambi Sub-District, Jember Regency. By doing an observation, interview, and documentation, this study finds the Ngalak contract tradition is not complying with maqashid al-sharia. This study argues the approval of the debt and trading in the tradition is directed to the human benefit. In fact, the Ngalak contract tradition becomes the way to take profits by traders and middlemen who hurt the farmers. Islamic economics may provide two solutions, namely using a salam contract and develop the Islamic cooperative.